Idiopathic REM sleep behaviour disorder: a case report - Niranjan Hebbar YR; Ashutosh Dash; Dhananjay Patro; Th Bihari Singh (Open Journal of Psychiatry and Allied Sciences, 2017)
This case reports one of the rare parasomnias, i.e. rapid eye movement (REM) sleep behaviour disorder (RSBD), and shows that accurate diagnosis and management results in great outcome.